PENGARUH PEMAHAMAN ATC TERHADAP COCKPIT PROCEDURE DALAM EFEKTIVITAS PENANGANAN EMERGENCY AND ABNORMAL SITUATION DI PERUM LPPNPI CABANG KUPANG - Maryani Afila Revandi; Wasito Utomo; Arnaz Olieve (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This study aims to determine the effect of understanding the cockpit procedure on emergency and abnormal situational awareness for procedural approach control guide personnel in Kupang approach control unit, in order to be able to maintain or improve their performance in providing air traffic control services in accordance with the recommendations set by the International Civil Aviation. Organization (ICAO). Perum LPPNPI Kupang Branch provides approach control services in a procedural manner by having an increasing amount of traffic every year and having international flights. This condition makes the potential for emergency and abnormal situations at Perum LPPNPI Kupang Branch to increase, so ATC personnel must be ready to assist pilots in dealing with emergency and abnormal situations. Especially in dealing with emergencies that occurred on the SJY-182 aircraft at Perum LPPNPI Soekarno-Hatta Jakarta Branch, this did not happen at Perum LPPNPI Kupang Branch.